PENGARUH KUALITAS PELAYANAN, KEADILAN BAGI HASIL DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH GEBU PRIMA, MEDAN - Nasution, Khoirul Amri; Wahyuni, Sri Fitri (ITB AAS Indonesia Surakarta, 2024)
Abstract The growth of Islamic banking in Indonesia lags behind conventional banking, primarily due to insufficient customer loyalty. To enhance market share, Islamic banking providers in Indonesia must prioritize customer satisfaction, as satisfied customers are more inclined to remain loyal. This research aims to explore the interrelationships among service quality, fairness in profit-sharing, customer satisfaction, and customer loyalty. The study involves four key variables: service quality, profit-sharing fairness, and customer satisfaction as independent factors, and customer loyalty as the dependent factor. A simple random sampling method was employed, surveying 364 active customers, resulting in 78 valid responses. Findings indicate that service quality, profit-sharing fairness, and customer satisfaction collectively exert a significant influence on customer loyalty at BPRS Gebu Prima. The study reveals that these factors explain 47.6% of customer loyalty variance, with the remaining 52.4% influenced by unexplored variables beyond the scope of this research.